Tutuh Nya' Tiop, Akal Nya' Midop, Local Wisdom and Cultural Sustainability in Education - Paramitha, Elizabeth; Sutrisno, Hery; Bintang, Pianus; Waruwu, Marinu; Halida, Halida (Universitas Tanjungpura, 2026)
Ka' Jubata,